1985
DOI: 10.1073/pnas.82.18.6030
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of prostaglandin D2 to 9 alpha, 11 beta-(15S)-trihydroxyprosta-(5Z,13E)-dien-1-oic acid (9 alpha, 11 beta-prostaglandin F2): a unique biologically active prostaglandin produced enzymatically in vivo in humans.

Abstract: Transformation of prostaglandin D2 to 9cv,11,8-(15S)-trihydroxyprosta-(5Z,13E)-dien-l-oic acid (9a,11j3-prostaglandin F2): A unique biologically active prostaglandin produced enzymatically in vivo in humans (11-ketoreductase/11-epiprostaglandin Communicated by Charles R. Park, April 17, 1985 ABSTRACTIn vitro studies examining the metabolic transformation of prostaglandin D2 (PGD2) by human liver were conducted. PGD2 was found to be converted by a NADPH-dependent enzyme in the 100,000 x g supernatant of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 14 publications
1
59
1
Order By: Relevance
“…by human liver in vitro, Roberts and co-workers have provided convincing evidence that PGD2 is converted exclusively to 9a,1 1f-PGF2 (10). They have also shown that after infusion of radiolabeled PGD2 in a normal volunteer, at least 13 ofthe PGF ring compounds isolated in the urine had 9a, 1 (10).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…by human liver in vitro, Roberts and co-workers have provided convincing evidence that PGD2 is converted exclusively to 9a,1 1f-PGF2 (10). They have also shown that after infusion of radiolabeled PGD2 in a normal volunteer, at least 13 ofthe PGF ring compounds isolated in the urine had 9a, 1 (10).…”
Section: Introductionmentioning
confidence: 84%
“…shown that the predominant route of metabolism is via initial formation of the 1 l3-hydroxyl epimer of PGF2a, 9a, 1 If3-PGF2 (10)(11)(12). On examining the metabolic transformation of PGD2…”
Section: Introductionmentioning
confidence: 99%
“…The PGF 2α has been shown to induce uterine constriction, contraction of coronary arteries and raise blood pressure (Makino et al, 2007;Camu et al, 1992). The 9α,11ÎČ isomer of PGF 2 produces similar biological effects but it inhibits ADP-induced platelet aggregation whereas PGF 2α is devoid of such activity (Liston and Roberts, 1985). AKR1C3 (PGF synthase) has an active site which is capable of reducing both the endoperoxide group of PGH 2 and the aldehyde group of PGD 2 .…”
Section: C) Prostaglandinsmentioning
confidence: 99%
“…The urinary excretion (mean±SE) of 9α,11ÎČ-PGF 2 Eur Respir J 1998;12: 345-350. and N τ -methylhistamine, was measured before and after exercise challenge in a group of asthmatics with a history of EIB. The major cyclooxygenase product of mast cells PGD 2 , is metabolized in the lung, via the action of the reduced nicotinamide adeine dinucleotide phosphate (NADPH)-dependent enzyme 11-ketoreductase to 9α, 11ÎČ-PGF 2 , and is excreted intact into the urine [24]. Since PGD 2 production in humans is restricted almost exclusively to the mast cell [25], PGD 2 and its metabolites may be employed as mast cell markers.…”
Section: Aamentioning
confidence: 99%